Environment drives spatiotemporal patterns of clonality in white spruce (Picea glauca) in Alaska - Würth, David G.; Eusemann, Pascal; Trouillier, Mario; Burras, Allan; Burger, Andreas; Wilmking, Martin; Roland, Carl A.; Juday, Glenn Patrick; Schnittler, Martin (Canadian Journal of Forest Research, 2018)
Many plant species reproduce by cloning if environmental conditions are unfavorable for sexual reproduction. To test the alternative hypotheses, whether cloning is an “exit strategy” or caused by selection, clonal growth in white spruce (Picea glauca (Moench) Voss) was investigated in three stands in Alaska, each consisting of a core (closed forest) plot and an edge (tree-line) plot. In total, 2571 trees were mapped and genotyped with 11 single sequence repeat (SSR) markers. The proportion of clonal trees follows a moisture gradient and was lowest in the dry Interior basin (4.5%), followed by the sites at the Alaska Range (9.0%) and the Brooks Range (21.7%). At the two latter sites, clonal growth was more frequent in the edge plot. A comparison among 960 aged trees revealed that clonal growth becomes more likely with increasing age and continues over the life span of a tree. Genetic data do not indicate any genetic predisposition for cloning. Clonal growth in white spruce most likely takes place via layering and depends on environmental conditions. Because performance of the trees, and therefore likely plant reproductive success, is lower in plots with a high proportion of clones, selection for clonal growth seems to be highly unlikely. Plusieurs espèces végétales se reproduisent par clonage lorsque les conditions environnementales ne sont pas favorables à la reproduction sexuée. Pour tester les hypothèses alternatives selon lesquelles le clonage est une « stratégie de sortie » ou est provoqué par la sélection, la croissance clonale de l’épinette blanche (Picea glauca (Moench) Voss) a été étudiée dans trois peuplements de l’Alaska, dans chacun desquels on a établi une placette d’intérieur (forêt fermée) et une placette de bordure (limite des arbres). Au total, 2571 arbres ont été cartographiés et génotypés à l’aide de 11 marqueurs SSR. La proportion d’arbres clonaux suit un gradient d’humidité et était la plus faible dans le bassin intérieur sec (4,5 %), suivi par les stations de la chaîne de l’Alaska (9,0 %) ...